2020
DOI: 10.1002/cbdv.201900663
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diversity from Arid‐Land Plants: Valorization of Terpenes and Biotransformation Products

Abstract: Asteraceae plants from arid lands are a source of biomass, resin and latex rich in terpenoids with diverse biological effects. Thirty‐six previously isolated terpenes, comprising sesquiterpenes, diterpenes, triterpenes and quassinoids, isolated from arid‐land plants and a series of metabolites from the biotransformation of some lead compounds were evaluated against insect pests (Spodoptera littoralis, Leptinotarsa decemlineata, Myzus persicae and Rhopalosiphum padi), cells (insect, hamster, murine and human tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…In the case of M. persicae, only settling inhibition was considered, which was found to be affected by guayulins C and D, isoargentatin B and argentatin B. This contrasts with the findings of Bailen et al (2020) [32], who found that argentatin B and guayulin B had no antifeedant effects on M. persicae. However, it should be noted that the testing method was different (they tested direct antifeedant activity, whereas we inferred antifeedant activity as settling inhibition).…”
Section: Discussionmentioning
confidence: 74%
“…In the case of M. persicae, only settling inhibition was considered, which was found to be affected by guayulins C and D, isoargentatin B and argentatin B. This contrasts with the findings of Bailen et al (2020) [32], who found that argentatin B and guayulin B had no antifeedant effects on M. persicae. However, it should be noted that the testing method was different (they tested direct antifeedant activity, whereas we inferred antifeedant activity as settling inhibition).…”
Section: Discussionmentioning
confidence: 74%
“…β-eudesmol, one of the main compounds in CZ-EO, displays antitrypanosomal activity (EC 50 = 5.45 µg/mL) against Trypanosoma brucei brucei GUTat 3.1 and displays low cytotoxicity to MRC-5 cells (CC 50 > 100 µg/mL, SI > 18) [39]. Bailen and co-workers reported the antileishmanial and trypanocidal activities of β-eudesmol against Leishmania infantum (IC 50 = 52.5 µg/mL) and Trypanosoma cruzi (IC 50 > 100 µg/mL) [40]. The EOs from Guatteria friesiana and Guatteria pogonopus leaves, which are rich in β-eudesmol, display trypanocidal action against the T. cruzi bloodstream trypomastigote and epimastigote forms, with IC 50 values of 11.9 and 28 µg/mL against epimastigotes and 10.7 µg/mL and 41.3 µg/mL against trypomastigotes, respectively [41].…”
Section: Discussionmentioning
confidence: 99%
“…Biotransformations of terpenoids can modify the biological activities of the starting compounds [9] and are also used to study structure-activity relationships of bioactive compounds [10]. In this context, Mucor plumbeus, with a broad substrate specificity [11,12], has been used in biotransformations of diterpenes to develop models to explain their hydroxylations [13][14][15][16][17] and for the biotransformation of an africanane sesquiterpene to give epoxy Plants 2021, 10, 891 2 of 14 derivatives with improved insect antifeedants and insecticidal effects [18].…”
Section: Introductionmentioning
confidence: 99%
“…candial along with several known compounds. Furthermore, 3α-hydroxypelenolide (3), previously known as hydroxypelenolide [4], was biotransformed by Mucor plumbeus to give 1β, 10α-epoxide (9) and a cadinane derivative (10). The latter was formed by an acid rearrangement produced in the culture medium, not by the enzymatic system of the fungus.…”
Section: Introductionmentioning
confidence: 99%